NALAR MITIS DALAM KONSEP MARTIR JIHADIS MELALUI HERMENEUTIKA MUHAMMED ARKOUN ATAS AYAT JIHAD - Mahbub Ghozali (IAT IAIN Pontianak, 2022)
Abstract This study aims to reveal the meaning of jihad in a modern context by Mohammed Arkoun’s hermeneutics approach. The definition of jihad, which is always identified with the sacrifice of body in the way of Allah, always leaves a lingering problem. Radicalism in the name of religion and the slogan of jihad towards the death of martyrs has been widely heard. To respond to this, this study uses qualitative methods with the type of literature study research. This research found that the meaning of the verse which textually means war can be interpreted differently by referring to the consciousness formed in each verse. Awareness of the meaning of the verse of jihad requires one to understand it in a variety of actions that are not only limited to soul sacrifice. Jihad can be carried out in all other ways that are relevant to the context and the demands of the situation in every human condition and capability. Penelitian ini bertujuan untuk mengungkapkan makna jihad dalam konteks modern dengan menggunakan hermeneutika Mohammed Arkoun. Definisi jihad yang selalu diidentikkan dengan pengorbanan jiwa di jalan Allah, selalu menyisakan problem yang berkepanjangan. Radikalisme atas nama agama dan selogan jihad untuk menuju kematian syahid banyak didengarkan. Untuk merespon hal tersebut, penelitian ini menggunakan metode kualitatif dengan jenis penelitian studi pustaka. Penelitian ini menemukan bahwa makna ayat yang secara tekstual bermakna perang, dapat dimaknai berbeda dengan mengacu pada kesadaran yang dibentuk dalam setiap ayat. Kesadaran atas makna ayat jihad menuntut seseorang untuk memahaminya dalam berbagai macam tindakan yang tidak hanya terbatas pada pengorbanan jiwa. Jihad dapat dilakukan dengan segala cara lain yang relevan dengan konteks dan tuntutan keadaan di setaip kondisi dan kemampuan manusia.